Formation Of Hierarchical Porous Iron Oxide And Their Application In Reducing Cr(Vi) - Ong, Yee Chin (Universiti Sains Malaysia, 2017)
Cr(VI) is heavy metal of high toxicity and has been classified as human carcinogen. Cr(VI) enters into environment from sources such as leather and tanning, alloys and steel manufacturing and rubber manufacturing industries. This study investigated the applicability of hierarchical porous iron oxide for the removal of Cr(VI) from aqueous solution. The hierarchical porous structures were synthesized by direct thermal oxidation of iron wire in water vapour atmosphere. The synthesized hierarchical porous iron oxide were characterized by Field Emission Scanning Electron Microscope (FESEM), High Resolution Transmission Electron Microscope (HRTEM) and Raman spectroscopy. Oxidation parameters investigated were the effect of oxidation temperature, time and presence of water vapour. Oxidation at different temperatures resulted in the formation of nanowires at 400 ºC, nanosheets at 500 ºC, hierarchical porous structure at 600 ºC and blades formed at 700 ºC. Hierarchical porous structure formed when oxidation carried out in water vapour for 400 ºC to 600 ºC and blades structures was formed at 700 ºC in water vapour. Different oxidation time at 500 ºC in water vapour was conducted to investigate the growth of nanostructures on iron wire. A mixture of nanowires and blades formed at 15 min of oxidation time and more blades formed with few nanowires after 30 min. Hierarchical porous structures were observed after 1 hour oxidation. The growth of nanostructures on iron oxide was suggested to follow the stress-driven mechanism. The longer oxidation time leads to lateral growth of nanowires which then turn to blade structure and hierarchical structures formed when the walls of blade meet. The reduction percentage of Cr(VI) at pH 2 is the highest for sample oxidised at 500 ºC for 1 hour (59.09 %) compared to the one at 30 minutes (58.55 %) and 15 minutes (38.64 %), respectively.